Stem Cell- and Stem Cell-Free-Based Therapies: Pros and Cons - Mobarak, Halimeh; Rahbarghazi, Reza; Mahdipour, Mahdi (West Kazakhstan Medical Journal, 2023)
The efficiency of stem cell (SC)-based therapies has been proven in numerous animal and human studies. Along with the differentiation into several lineages, it is quite evident that SCs convey significant therapeutic effects in a paracrine manner via releasing various nano-sized extracellular vesicles (EVs) containing cytokines and bioactive factors. Notably, recent trials have stated the lack of stability and durability of the transplanted SCs at the site of injury for long periods, leading to the restrictions of SC in regenerative outcomes. Thus, EVs especially exosomes (Exos) gained much attention for therapeutic purposes and delivery purposes to the injury site. In contrast to whole-SC-based therapies, Exos can be used with fewer side effects. However, it should not be forgotten that both whole-SC- and cell-free-based options possess inherent pros and cons that necessitate being carefully evaluated before application in the clinical setting. Here, the effectiveness and limitations associated with whole-SCand SC-free-based therapies in the clinical setting are briefly discussed.